Understanding critical health literacy: a concept analysis - Sykes Susie; Wills Jane; Rowlands Gillian; Popple Keith (BMC, 2013)
Abstract Background Interest in and debates around health literacy have grown over the last two decades and key to the discussions has been the distinction made between basic functional health literacy, communicative/interactive health literacy and critical health literacy. Of these, critical health literacy is the least well developed and differing interpretations of its constituents and relevance exist. The aim of this study is to rigorously analyse the concept of critical health literacy in order to offer some clarity of definition upon which appropriate theory, well grounded practice and potential measurement tools can be based. Method The study uses a theoretical and colloquial evolutionary concept analysis method to systematically identify the features associated with this concept. A unique characteristic of this method is that it practically combines an analysis of the literature with in depth interviews undertaken with practitioners and policy makers who have an interest in the field. The study also analyses how the concept is understood across the contexts of time, place, discipline and use by health professionals, policy makers and academics. Results Findings revealed a distinct set of characteristics of advanced personal skills, health knowledge, information skills, effective interaction between service providers and users, informed decision making and empowerment including political action as key features of critical health literacy. The potential consequences of critical health literacy identified are in improving health outcomes, creating more effective use of health services and reducing inequalities in health thus demonstrating the relevance of this concept to public health and health promotion. Conclusions While critical health literacy is shown to be a unique concept, there remain significant contextual variations in understanding particularly between academics, practitioners and policy makers. Key attributes presented as part of this concept when it was first introduced in the literature, particularly those around empowerment, social and political action and the existence of the concept at both an individual and population level, have been lost in more recent representations. This has resulted in critical health literacy becoming restricted to a higher order cognitive individual skill rather than a driver for political and social change. The paper argues that in order to retain the uniqueness and usefulness of the concept in practice efforts should be made to avoid this dilution of meaning.